BK virus nephropathy complicated with meningoencephalitis after kidney transplantation. (16th December 2013) - Rocha, Ana; Faria, Sameiro; Costa, Teresa; Marques, Laura; Freitas, Cristina; Mota, Conceição
Abstract BK disease is an opportunistic infection in organ transplant recipients and patients with other cellular immunodeficiencies. To the best of our knowledge, we report the second case of BK meningoencephalitis associated with nephropathy in a kidney transplant recipient. A 15‐yr‐old boy underwent a cadaveric kidney transplant without complications; however, 11 wk after the transplantation, he was admitted to the hospital for graft dysfunction and cytopenia, which were confirmed by BK nephropathy (plasma viral replication and histological evidence). Four days after his hospital admission, he developed a high‐grade fever and headache. CSF analysis revealed pleocytosis with a positive PCR for BK virus. Reduction in immunosuppression and supportive care conducting cycles of immunoglobulin and cidofovir were successful in treating the patient. BK meningoencephalitis should be considered in kidney transplant recipients who present with signs and symptoms of meningoencephalitis.